Inflammatory-Driven Angiogenesis in Bone Augmentation with Bovine Hydroxyapatite, B-Tricalcium Phosphate, and Bioglasses: A Comparative Study - Vlad M. Anghelescu; Ioana Neculae; Octavian Dincă; Cristian Vlădan; Claudiu Socoliuc; Mirela Cioplea; Luciana Nichita; Cristiana Popp; Sabina Zurac; Alexandru Bucur (Journal of Immunology Research)
Introduction. The clinical use of bioactive materials for bone augmentation has remained a challenge because of predictability and effectiveness concerns, as well as increased costs. The purpose of this study was to analyse the ability to integrate bone substitutes by evaluating the immunohistochemical expression of the platelet endothelial cell adhesion molecules, vascular endothelial growth factor, collagen IV, laminin, and osteonectin, in the vicinity of bone grafts, enabling tissue revascularization and appearance of bone lamellae. There is a lack of in vivo studies of inflammatory-driven angiogenesis in bone engineering using various grafts. Methods. The study was performed in animal experimental model on the standardized monocortical defects in the tibia of 20 New Zealand rabbits. The defects were augmented with three types of bone substituents. The used bone substituents were beta-tricalcium phosphate, bovine hydroxyapatite, and bioactive glasses. After a period of 6 months, bone fragments were harvested for histopathologic examination. Endothelial cell analysis was done by analysing vascularization with PECAM/CD31 and VEGF and fibrosis with collagen IV, laminin, and osteonectin stains. Statistical analysis was realized by descriptive analysis which was completed with the kurtosis and skewness as well as the Kruskal-Wallis and Mann-Whitney statistical tests. Results. The discoveries show that the amount of bone that is formed around beta-tricalcium phosphate and bovine hydroxyapatite is clearly superior to the bioactive glasses. Both the lumen diameter and the number of vessels were slightly increased in favor of beta-tricalcium phosphate. Conclusion. We can conclude that bone substitutes as bovine bone and beta-tricalcium phosphate have significant increased angiogenesis (and subsequent improved osteogenesis) compared to the bioactive glass. In our study, significant angiogenesis is linked with a greater tissue formation, indicating that in bone engineering with the allografts we used, inflammation has more benefic effects, the catabolic action being exceeded by the tissue formation.